Robust Fixed-Time Stability: Application to Sliding-Mode Control - Moulay, Emmanuel; Lechappe, Vincent; Bernuau, Emmanuel; Plestan, Franck (IEEE transactions on automatic control, 2022)
This article deals with robust fixed-time stability and stabilization. First, new global robust fixed-time stability results are proposed for scalar systems by using constant and variable exponent coefficients. Then, they are applied to global robust fixed-time stabilization of a class of uncertain nonlinear second-order systems by using sliding-mode control. All the results are illustrated in simulation.